1993
DOI: 10.1073/pnas.90.8.3725
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 12 and tumor necrosis factor alpha are costimulators of interferon gamma production by natural killer cells in severe combined immunodeficiency mice with listeriosis, and interleukin 10 is a physiologic antagonist.

Abstract: Listeriosis in mice with the severe combined immunodeficiency (SCID) mutation is an established model in vivo and in vitro of interferon y(IFN-y)-dependent macrophage activation by natural killer (NK) cells during the development of natural immunity. We demonstrate that IFN-y production from SCID splenocytes is stimulated by interleukin (IL) 12, tumor necrosis factor a (TNF-a), and IL-2 but is inhibited by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
488
4
5

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 710 publications
(521 citation statements)
references
References 25 publications
(8 reference statements)
24
488
4
5
Order By: Relevance
“…Previous studies have also suggested that TNF- § in combination with or without IFN-+ plays an important role in activating resident macrophages to kill intracellular pathogens such as L. monocytogenes and T. gondii [4, [38][39][40][41][42]. However, no correlation was observed between the increase of resistance and in vitro TNF- § production in this study (Fig.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Previous studies have also suggested that TNF- § in combination with or without IFN-+ plays an important role in activating resident macrophages to kill intracellular pathogens such as L. monocytogenes and T. gondii [4, [38][39][40][41][42]. However, no correlation was observed between the increase of resistance and in vitro TNF- § production in this study (Fig.…”
Section: Discussioncontrasting
confidence: 58%
“…5D, left panel). Besides IFN-+ , other cytokines such as TNF- § have also been proposed to be an important factor in resistance to intracellular pathogens [4, [38][39][40][41][42]. However, in contrast to IFN-+ , substantial levels of TNF- § were produced by + c -/-(y) -Rag-2 -/-splenocytes with or without exogenous APC fractions in response to L. monocytogenes, and no apparent correlation was observed between the amounts of TNF- § and the susceptibility to L. monocytogenes (Fig.…”
Section: Adoptive Transfer Of Ifn-q -Producing Apc Provides Resistancmentioning
confidence: 99%
“…It is secreted by a variety of cells including T helper cells, monocytes, macrophages, B cells, and keratinocytes (Moore et al 1993). In vitro studies demonstrate that IL-10 limits production of cytokines such as IL-1, IL-6, TNF-α, granulocyte-macrophage colony-stimulating factor, and IL-12, the generation of reactive oxygen intermediates, and the expression of surface MHC class II and co-stimulatory molecules (Tripp et al 1993;Fiorentino et al 1991;D'Andrea et al 1993). Furthermore, IL-10 directly inhibits IFN-γ production and activity in the innate and adaptive immune system via its action on NK and T cells (Chomarat et al 1993;Moore et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…4 We have focused on TNF-␣ as a proinflammatory cytokine in the following experiments because it is secreted by macrophages after the phagocytosis of parasites and IFN-␥ is secondarily secreted by NK cells following stimulation of IL-12 and TNF-␣. 32 No TNF-␣ was observed in any organs or the serum of untreated mice (data not shown). Much higher amounts of TNF-␣ were observed in the liver and spleen of saline-pretreated mice after i.v.…”
Section: Increases In the Liver And Spleen After Lipoplex Injection Amentioning
confidence: 91%